Infrastrutture stradali più sicure. Fase I: i criteri XXVI Convegno nazionale stradale - AIPCR Comitato Tecnico C1 (Proceedings e report, 2010)
This monograph is a PIARC technical report which will be distributed on the occasion of the XXVI National PIARC Conference to be held in Rome on 27-30 October 2010. The report has been drafted by members of the C1 Technical Committee of the PIARC, comprising academics, road management bodies and road designers, chaired by Prof. Domenichini, a lecturer at the University of Florence. The report is divided into three chapters that address three extremely topical issues in the field of road infrastructure safety: the European Directive 2008/96/EC on road infrastructure safety management; analysis of the human factor in road accidents, and transition areas for the protection of urban sections of extra-urban road systems.